Plan estratégico para la empresa vidriería romero y su incidencia en el crecimiento empresarial, cantón La Maná, período 2014 - 2018 - Palma Proaño, Eric Wilson (2015)
This thesis research was to design a strategic plan for the Company Glassmaking Romero purpose and its impact on business growth during the period 2014-2018, seeking to improve the quality of service to clients through a guaranteed service; which it was essential to examine the external and internal situation of the company through the SWOT analysis. For purposes of the study, deductive, analytical and synthetic methods are applied, which allowed to learn about the reality of the company; likewise through SWOT analysis and surveys of customers, staff and general manager by which an organization problems with their respective functions thereof significantly affecting growth were detected in terms of the absence of a strategic direction, Business and user satisfaction. In addition it was found affirmatively the general hypothesis that the design of a Strategic Plan for glassmaking Romero will impact positively on business growth; because by structuring a strategic direction, a training plan, manual functions have a direct impact on product quality and the development of a company. Importantly currently glassmaking Romero does not have a strategic plan to focus their efforts toward a common goal, for this reason it is important to design the plans and actions with their respective budgets. For the above reasons the implementation of a strategic plan is considered necessary to improve the business growth strategies and actions that strengthen the company exposed in the pursuit of customer satisfaction and profitability for the owner.